Hegemoni Negara terhadap Seni Reyog Ponorogo - Jusuf Harsono (ARISTO, 2019)
The existence of art Reyog Ponorogo until now it is a traditional art Ponorogo Regency, community pride even in politics is needed by the existence of the political elite, nevertheless the availability of the arts it politically sufficiently interesting to observe in the political dynamics localized in Ponorogo. How the political elite or the state doing my hegemony on all aspects of this art Reyog Ponorogo. This study using several methods to get clarification on the problems on some of them are with the interview, observation, and documentation. The result showed that elite politics or the state has made various ways to Hegemony art Reyog Ponorogo as a mass mobilization of effective local. especially in the dynamics of politics.